Hydrogen Sulfide Affects Radical Formation in the Hippocampus of LPS Treated Rats and the Effect of Antipsychotics on Hydrogen Sulfide Forming Enzymes in Human Cell Lines - Sommer, Olaf; Aug, Rosana L.; Schmidt, Andreas J.; Heiser, Philip; Schulz, Eberhard; Vedder, Helmut; Clement, Hans-Willi (Frontiers in Psychiatry, 2018)
Objectives: Psychiatric disorders, such as schizophrenia and other neuroinflammatory diseases are accompanied by an increase in the oxidative stress and changes in the immune system and in the metabolic, hormonal and neurological components of the central nervous system (CNS). Hydrogen sulfide (H2S) is a gaseous molecule that is endogenously produced in the peripheral and central nervous system through cysteine by the following major H2S producing enzymes in the brain: cystathionine-γlyase (CSE), cystathionine ß-synthase (CBS) and 3-mercaptopyruvate sulfurtransferase (MPST). The physiological effects of H2S are broad, with antioxidative properties being a major role in the body. The aims of our investigation were to analyze the central nervous antioxidant, metabolic and neuronal effects in the hippocampus of the rat after inflammatory peripheral lipopolysaccharide (LPS) treatment; and to examine the effects of antipsychotics on the expression of these enzymes in human cell lines. Material and Methods: Male Lewis rats (250 g) received an i.p. LPS injection (1 mg/kg) 24 h before microdialysis experiments. Conscious rats were infused via these probes (1.5 μl/min) with a radical scavenger 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine (CMH) in Krebs-Ringer solution. Sodiumhydrogensulfide (NaHS, 10 μg/min) was infused after a 2- h baseline for 1 h. Corticosterone, glutamate, glucose and lactate were measured by Elisa. Reactive oxygen species (ROS) were detected by electron spin resonance spectroscopy (ESR). The impact of the antipsychotics haloperidol, clozapine, olanzapine and risperidone on the expression of genes encoding the key enzymes of H2S synthesis was studied at the human neuroblastoma SH-SY5Y and monocytic U-937 cell lines. The cells were incubated for 24 h with 30 μM antipsychotic following which mRNA levels were measured by polymerase chain reaction. Results: Microdialysate glucose and lactate levels dramatically increased in the hippocampus of LPS untreated rats by local application of NaHS. By contrast, in the LPS pretreated rats, there was no effect of NaHS infusion on glucose but a further significant increase in microdialysate lactate was found. It was LPS pretreatment alone that particularly enhanced lactate levels. There was a marked increase in hippocampal microdialysate glutamate levels after local NaHS infusion in LPS untreated animals. In LPS treated rats, no change was observed by NaHS, but LPS itself had the strongest effect on microdialysate glutamate levels. Microdialysate corticosterone levels were reduced by NaHS in both LPS pretreated and untreated rats. The formation of free radicals in the hippocampus significantly reduced in LPS pretreated rats, while in LPS untreated rats a significant increase was observed after NaHS infusion. In human SH-SY5Y and U-937 cells, all three major enzymes of H2S-Synthesis, namely cystathionine-γ-lyase, cystathione ß-synthase and 3-mercaptopyruvate sulfurtransferase, could be detected by PCR. The antipsychotics haloperidol, clozapine, olanzapine and risperidone affected all three enzymes in different ways; with haloperidol and risperidone showing major effects that led to reductions in CBS or CSE expression. Discussion: The local application of NaHS in the hippocampus of the rat strongly affected glucose, lactate and glutamate release. Contrastingly, in LPS pretreated rats, a decreased radical formation was the only effect found. H2S synthetizing enzymes may be involved in antipsychotic mechanisms, although no clear common mechanism could be found.